Resolute - Campbell, Jack (Naval officer) (Campbell, Jack (Naval officer). Lost fleet: outlands., 2022)
"Admiral John "Black Jack" Geary must battle dangers both within and without the Alliance, in this exciting continuation of the New York Times bestselling series. Geary knows that some political factions in the Alliance were just trying to get rid of him when he was assigned to escort a diplomatic and scientific mission to the far reaches of humanity's expansion into the galaxy . . . and beyond. But he views his mission as both a duty and an opportunity to make things better wherever he can. And when a crippled Rift Federation ship tumbles out of jump space, Geary leaps into action. But the survivors' story isn't completely adding up. As Geary investigates, he soon finds himself fending off spies and assassins while leading the fleet as it fights its way across space controlled by the mysterious and hostile aliens whom humans call enigmas. Challenges arrive at every turn, including an unknown alien species that invites the fleet to visit one of their star systems. With little information to go on, Geary must weigh the benefits of potential new allies against the possibility of a trap. The fate of the fleet-and perhaps even the future of humanity-will depend on him making the right decision. If he can stay alive long enough to do that"--